Long term outcomes of patients with chronic inflammatory diseases after percutaneous coronary intervention. (14th October 2021) - Marcusohn, E; Zukermann, R; Roguin, A; Kobo, O
Abstract: Introduction: Patients with chronic inflammatory diseases are at increased risk for coronary artery disease. Aim: We aimed to assess the long-term outcomes of patients with chronic inflammatory diseases who underwent percutaneous coronary intervention. Methods: A Retrospective cohort study of all adult (>18 years) patients who underwent PCI in a large [1000 bed] tertiary care centerfrom January 2002 to August 2020. Results: A total of 12, 951 patients underwent PCI during the study period and were included in the cohort. The population of chronic inflammatory diseases includes 247/12, 951 [1.9%]; 70 with IBD and 173 with AIRD. The composite endpoint of mortality, ACS or CHF admission was more frequent in the inflammatory disease group (77.5% in AIRD group, 72.9% in the IBD group and 59.6% in the non-inflammatory group, p<0.001). The adjusted cox regression model found a statistically significant increased risk of the composite primary endpoints of around 40% for patients both with AIRD and IBD. The increased risk for ACS was 61% for AIRD patients and 37% for IBD patients. Patients with inflammatory diseases were found to have a significant increased risk CHF admission, while both IBD and AIED patients had a non-significant increased risk for mortality. Conclusion: Patients with AIRD and IBD are at higher risk for cardiovascular events also in long term follow up once diagnosed with CAD and treated with PCI. Funding Acknowledgement: Type of funding sources: None.